2020
DOI: 10.1029/2020gh000331
|View full text |Cite
|
Sign up to set email alerts
|

How Do Brazilian Fires Affect Air Pollution and Public Health?

Abstract: Fires burning across the Amazon in the summer of 2019 attracted global attention for the widespread destruction of natural ecosystems and regional smoke production. Using a combination of satellite fire observations and atmospheric modeling, Nawaz and Henze (2020, https://doi.org.10.1029/ 2020GH000268) provide new evidence for the widespread regional public health consequences attributed to these fires. They find that approximately 10% of premature deaths in Brazil due to fine particulate matter (PM 2.5) are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(55 reference statements)
0
7
0
3
Order By: Relevance
“…(3,20) As projeções climáticas regionais sugerem que os regimes de fogo na Amazônia irão se intensificar, afetando a qualidade do ar externo e interno em comunidades rurais e urbanas. (13,15,20,21)…”
Section: Queimadas Ou Incêndios Florestais?unclassified
See 2 more Smart Citations
“…(3,20) As projeções climáticas regionais sugerem que os regimes de fogo na Amazônia irão se intensificar, afetando a qualidade do ar externo e interno em comunidades rurais e urbanas. (13,15,20,21)…”
Section: Queimadas Ou Incêndios Florestais?unclassified
“…(55) Estudos ecológicos recentes sugerem uma ligação entre a exposição a altos níveis de MP 2,5 e o aumento da mortalidade por COVID-19, (56) embora as influências de outros fatores, como densidade populacional, fatores socioeconômicos e cumprimento das medidas de distanciamento social, também devam ser consideradas. (21,57) As populações mais vulneráveis à exposição à fumaça de incêndios florestais também são suscetíveis à infecção por SARS-CoV-2. A exposição à fumaça de incêndios florestais também pode aumentar a probabilidade de infecção por SARS-CoV-2, bem como a gravidade da COVID-19.…”
Section: Incêndios E Covid-19unclassified
See 1 more Smart Citation
“…Fire activities in the Amazon region occur mainly during the dry season (August to November). 9 However, a study from 2016 found that the duration of the dry season is lengthening; 10 For the Instituto Nacional de Persquisas Espaciais see http://www.inpe.br/queimadas extreme hydrological events (ie, frequent drought in 2005, 2010, and 2015 11 ) might also increase the frequency and severity of wildfires in the Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…To Johns Hopkins University [19], the possible relation between contact with PM2.5 and COVID-19 has special significance for public health in Brazil, where incidence and mortality rates are among the highest worldwide. People settled in the North Brazilian region, especially vulnerable communities, are particularly affected by high exposure; for instance, the mortality rate from COVID-19 among indigenous people is above the Brazilian average [20]. Moreover, there is evidence that the reported number of COVID-19 victims among the indigenous population are underestimated [21].…”
Section: Introductionmentioning
confidence: 99%